Cognitive Behavioral Therapy (Brief vs Standard Duration) for Schizophrenia - Naeem, Farooq (Oxford University Press, 2014)
There is some evidence from research that suggests that cognitive behavioral therapy for psychosis (CBTp) might offer some advantage if offered in combination with pharmacological treatments for people with schizophrenia. There are, however, limitations in its provision due to available resource and training issues. Brief forms of CBTp might be an alternative in settings with limited resources. Brief therapies have shown to be as effective as standard therapies for some nonpsychotic disorders. There is some evidence in favor of brief CBTp. We wanted to review the effects of brief CBTp for people with schizophrenia compared with standard CBTp. We searched the Cochrane Schizophrenia Group’s Trials Register for randomized controlled trials (RCTs) involving adults with schizophrenia or related disorders, comparing brief cognitive behavioral therapy for people with psychosis vs standard CBTp. We found only 7 studies which used a brief version of CBTp, but no study compared brief CBTp with CBTp of standard duration. There is a need for RCTs which compare brief with standard CBTp. This review also highlighted the need for setting standard criteria for CBTp dose. For this review, we considered brief CBTp to be delivered within 4 months and using 6–10 sessions.